2019
DOI: 10.1002/hep4.1411
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implementing a “FIB‐4 First” Strategy on a Pathway for Patients With NAFLD Referred From Primary Care

Abstract: Detection of advanced fibrosis in nonalcoholic fatty liver disease (NAFLD) is essential for stratifying patients according to the risk of liver‐related morbidity. Noninvasive methods such as vibration‐controlled transient elastography (VCTE) and Fibrosis‐4 index (FIB‐4) have been recommended to identify patients for further assessment. The aim of this study was to assess the potential impact of implementing a “FIB‐4 First” strategy to triage patients entering a NAFLD assessment pathway. The pathway for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 30 publications
(37 reference statements)
2
68
0
Order By: Relevance
“…Although FIB-4 showed a high negative predictive value for advanced liver fibrosis, it does not adequately rule-in advanced fibrosis. So, several referral pathways from primary health care settings have been proposed [8,9]. Davyduke et al suggested that vibration-controlled transient elastography (VCTE) could save up to 87% of further assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FIB-4 showed a high negative predictive value for advanced liver fibrosis, it does not adequately rule-in advanced fibrosis. So, several referral pathways from primary health care settings have been proposed [8,9]. Davyduke et al suggested that vibration-controlled transient elastography (VCTE) could save up to 87% of further assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Both the NFS and FIB-4 scores have considerable intermediate zones (~30%), even though both estimated formulae showed good negative predictive performance [6,7]. Because of the considerable intermediate zone and low positive predictive value of the FIB-4 system, several sequential algorithms based on the FIB-4 system have been suggested [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This staged risk-stratification model using FIB-4 and VCTE could obviate the need for up to 87% of further assessments. 144 Combining at-risk clinical characteristics (hazardous alcohol intake, elevated ALT, metabolic risk factors) with serum markers and VCTE in primary care programmes yielded many more diagnoses of advanced liver disease in patients with alcoholrelated liver disease or NAFLD. 145,146 These combined approaches are important, but require validation based on disease aetiology, ethnicity and prevalence, as well as consideration of regional socioeconomic limitations due to differing healthcare payor systems, access to US elastography, and specialist care.…”
Section: Combination Algorithmsmentioning
confidence: 99%
“…Addressing this gap, Davyduke and colleagues leveraged an NAFLD referral program within the catchment of the University of Alberta to compare a two‐stage approach with the existing single‐step VCTE‐based strategy. Specifically, they evaluated 560 patients between 16‐65 years of age with elevated alanine aminotransferase or steatosis on imaging who underwent VCTE on referral.…”
Section: Study Findingsmentioning
confidence: 99%